ROLE OF POLYMORPHISM OF GENES OF THE ANTIOXIDANT SYSTEM ENZYMES IN THE HABITUAL MISCARRIAGE GENESIS - K. V. Morozova; N. N. Lutsenko (IRBIS LLC, 2016)
The article is dedicated to the habitual miscarriage as to one of most actual problems of modern obstetrics and gynecology. In spite of multiple, formerly known reasons of such pathology, a lot of factors, predisposing to reproductive losses, still have not been studied. In last decades scientists have been focused on the studies of the role of genetic factors in the habitual miscarriage genesis. The genetically determined insufficiency of the antioxidant system can seriously undermine the organism homeostasis. It is interesting to study the influence of carriage of polymorphic variants of genes of the antioxidant system enzymes, as of a factor, negatively impacting the course of pregnancy